Modification of respiratory-chain enzyme activities in brown adipose tissue mitochondria by idebenone (hydroxydecyl-ubiquinone) - Rauchová, H; Drahota, Z; Bergamini, C; Fato, R; Lenaz, G (Journal of bioenergetics and biomembranes, 2008)
Idebenone (IDE), a synthetic analog of coenzyme Q, strongly activates glycerol phosphate (GP) oxidation in brown adipose tissue mitochondria. GP oxidase, GP cytochrome c oxidoreductase and GP dehydrogenase activities were all significantly stimulated by 13 muM IDE. Substituted derivatives of IDE acetyl- and methoxyidebenone had similar activating effects. When succinate was used as substrate, no activation by IDE could be observed. The activation effect of IDE could be explained as release of the inhibition of glycerol phosphate dehydrogenase by endogenous free fatty acids. NADH oxidoreductase activity and oxidation of NADH-dependent substrates were inhibited by IDE. The extent of the inhibition and IDE concentration dependence varied when various substrates were tested, being highest for pyruvate and lowest for 2-oxoglutarate. This study thus showed that the effect of IDE on various mitochondrial enzymes is very different and thus its therapeutic use should take into account its specific effect on various mitochondrial dehydrogenases in relation to particular defects of mitochondrial respiratory chain.
Keywords: Mitochondria; Male; Enzyme Activation; ubichinon; vztah mezi dávkou a účinkem léčiva; transport elektronů; mužské pohlaví; hnědá tuková tkáň; Electron Transport; kultivované buňky; Cricetinae; Animals; zvířata; Ubiquinone; aktivace enzymů; Cells, Cultured; Adipose Tissue, Brown; Dose-Response Relationship, Drug; mitochondrie; křečci praví